2013
DOI: 10.4103/0972-0707.105297
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between phosphoric acid and hydrochloric acid in microabrasion technique for the treatment of dental fluorosis

Abstract: Purpose:To compare the effectiveness of phosphoric acid (H3PO4)-pumice compound with conventional hydrochloric acid (HCl)-pumice compound in treating different severities of dental fluorosis with the microabrasion technique.Materials and Methods:Sixty-seven anterior teeth from seven patients with different severities of dental fluorosis were treated. In each patient, half of the teeth were treated with HCl-pumice compound and the other half with H3PO4-pumice compound (split-mouth design). Both treatment compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
(13 reference statements)
0
14
0
4
Order By: Relevance
“…The location and depth of the stain or spot are the most important factors for a successful treatment. As so, this procedure should be restricted to more superficial enamel and deeper lesions may require additional treatment …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The location and depth of the stain or spot are the most important factors for a successful treatment. As so, this procedure should be restricted to more superficial enamel and deeper lesions may require additional treatment …”
Section: Discussionmentioning
confidence: 99%
“…Although hydrochloric acid is presently used as a component of microabrasion pastes in concentrations up to 18%, its use at 36% as suggested by Chandra and Chawla is not currently advocated given the loss of tooth structure caused by high concentrations of hydrochloric acid …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement in esthetics of WSLs may be attributed to light reflection through this new surface, which is thought to act differently than light reflected from an untreated enamel surface. 29 However, to obtain this improvement, a relatively important layer of enamel has to be removed, and since the depth of WSLs can reach one third of the enamel thickness, this may not be accepted, because modern dentistry aims at maximal tissue preservation. Also, some studies showed that even if up to 360 µm are removed from the enamel surface during microabrasion, the WSL may still be visible in the end.…”
Section: Discussionmentioning
confidence: 99%
“…Both phosphoric acid (H 3 PO 4 )-pumice and (HCl)-pumice compounds presented effectiveness in treating different severities of dental fluorosis by using the microabrasion technique, however, the mean treatment time with the HCl-pumice was significantly lower than the one with H 3 PO 4 -pumice 4 . In addition, clinically, we have noted that stains are routinely removed with unrecognizable alterations.…”
Section: Discussionmentioning
confidence: 99%